(untitled) (Research, Society and Development, 2022)
This prospective cohort study aimed to evaluate by echocardiogram the cardiovascular effects of α2 agents associated with butorphanol in cats. A group of 18 mixed-breed cats with a mean weight of 3.65 + 0.7 kg, with an approximate age of 6 months. The cats were assigned in three groups, XB (Xylazine/butorphanol group) sedation with 0.5 mg/kg of xylazine and 0.5 mg/kg of butorphanol IM; DB (Dexmedetomidine/butorphanol group): sedation with 20 µg/kg of dexmedetomidine and 0.5 mg/kg of butorphanol IM; C: control group which received saline solution in volume approximated to those used in the other groups, IM. Echocardiographic variables as ejection fraction (Simpson’s method and M-mode) and left ventricular shortening fraction (M-mode), ejection volume, end-systolic volume and cardiac output (Teichholz), tissue Doppler E’ and A’ wave velocities and cardiac index were evaluated. There was a reduction in echocardiographic variables compared with the control group, being statistically significant for heart rate, ejection fraction (% by Simpson), shortening fraction (% in M-mode) and end-systolic volume in XB and DB groups, and tissue Doppler E’ and A’ wave velocity (m/s), E’/A’ ratio, cardiac output and cardiac index only in XB group. When compared to each other, XB and DB differed significantly in the tissue Doppler E’ and A’ wave velocity (m/s), and E’/A’ ratio. Xylazine was more deleterious than dexmedetomidine in most of the variables evaluated, leading to a significant reduction in cardiac output and cardiac index at the doses used in this study.